Prevalence of temporomandibular joint disfunction in children - Masitoh, Siti; Kurnikasari, Erna; Rikmasari, Rasmi (Padjadjaran Journal of Dentistry, 2007)
The aim of this study is to get the description on TMJ dysfunction as well as its symptoms including clicking, crepitation, jaw opening restriction and muscle pain in children. Thus the result can be used as an input to the program of TMJ dysfunction prevention and treatment for the children in SDN Sirnasari Village, Ciptasari Pamulihan Subdistrict, Sumedang District. This study is descriptive study using survey technique. The samples for the study are 79 children in elementary school taken by random sampling technique with stratification. TMJ dysfunctions with clicking and crepitation symptoms were detected by palpating and using a stethoscope. Deviation, deflection, and jaw opening restriction symptoms were found out by visual examination. Whereas pain in TMJ supporting muscles was also detected by palpating. The result of the study shows that the number of children developing TMJ dysfunction with symptom of clicking is 34 children (43.03%), crepitation are 4 children (5.06%), deviation are 13 children (16.45%), deflection are 17 children (21.51%), jaw opening restriction are 49 children (62.02%), and pain in TMJ supporting muscles are 69 children (87.34%). From the study, it can be concluded that the highest frequency of TMJ dysfunction symptom in SDN Sirnasari children is a pain in TMJ supporting muscles. It is followed by jaw opening restriction, clicking, deflection, deviation, and the last is crepitation.